Implementation of Among System in ECCE Quality Assurance - Nur Rahadian; Kurotul Aeni; Diana Diana (Universitas Negeri Semarang, 2024)
The purpose of the study was to determine the Implementation of the Among System in Early Childhood Care Education (ECCE) Quality Assurance focus on the implementation of the Among System on aspects of Local Potential-Based Curriculum Development, Local Wisdom-Oriented Learning, and Capacity Building of Educators and Education Personnel at the ECCE institution. This research uses a descriptive qualitative approach, with data collection techniques and data analysis using the Systematic Literature Review method. The results of the study found that the Implementation of the Among System in ECCE Quality Assurance with emphasis on the Implementation of the Among System on ECCE Curriculum Development based on local potential has the opportunity to be carried out based on the similarity of intentions, goals, and results to be achieved by the ECCE curriculum, both the 2013 Curriculum and the Merdeka Belajar Curriculum, with the idea of education within the Among System. Implementation of Among System in ECCE Quality Assurance with emphasis on the Implementation of the Among System on ECCE Learning Oriented to Local Wisdom is learning that gives the widest freedom to children, as long as there is no danger that threatens children, with a learning orientation to local wisdom delivered through: folk songs and crafts (weaving, batik, jumping, etc.); local fairy tales, both historical and mythological; environmental knowledge (religion, biology, geography, science). Implementation of Among System in ECCE Quality Assurance with emphasis on the Implementation of the Among System on Improving the Quality of ECCE Educators and Education Personnel is the implementation of Among's three philosophies: Ing Ngarso Sung Tulodho, Ing Madyo Mangun Karso, and Tut Wuri Handayani as a reference for the quality level of ECCE educators and education staff..